STUDI ISLAM PERSPEKTIF INSIDER DAN OUTSIDER - Fathoni, Imam; Ulfiah, Umi Hanik (Al Fattah Ejournal Sma Al Muhammad Cepu, 2023)
Insiders are religious scholars who come from their own religion (insiders). Meanwhile, outsiders are religious scholars who are not adherents of the religion concerned (outsiders). This article discusses the study of Islamic studies in the perspective of insiders and outsiders, this research uses a descriptive qualitative approach with data obtained from objective and accountable library research. The results of this research are: Islamic studies from an insider's perspective have produced several research results. Some general introductory books on Islam as a religion and civilization by single authors show the importance of a multidisciplinary approach. The fact of reality that is often discussed is that insider and outsider studies are closely related to the experiences of the West and Muslim scholars themselves in interpreting and understanding Islam. The issue at stake is whether outsider scholars of Islam are truly objective, and accountable, and have scientific validity from an insider's perspective